Study of Tasawuf: Existence as a Solution to the Crisis of Modern Society Due to the Current Development - Dila Wandasari; Yuni Tirtasari Siallagan; Ryan Irwansyah Pasaribu; Chuzaimah Batubara (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This article discusses Sufism, a solution to the spiritual crisis in modern society due to the times. This study aims to explain how Sufism can solve the dryness of spirituality—reintroducing the values of Sufism to the community so tshat they can be applied in everyday life. This research method is qualitative research conducted using observational surveys, document analysis, and information from online libraries such as ebooks. Based on research, human spirituality will increase again using Sufism, which can train humans not to follow lust, which tends to be strong towards materialism